Evaluasi Kinerja Pelayaran Hijau di Indonesia Menggunakan Metode Importance Performance Analysis dan Fishbone Analysis - Afyfah Ramadhani Dias Saputri; Muhammad Saiful Haki (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Green shipping is one of the efforts to reduce the negative impact of the shipping sector on the environment, but its implementation in Indonesia still faces various challenges. This study aims to identify factors that hinder the performance of green shipping in Indonesia and provide recommendations for improvements that can be applied to improve environmental sustainability in this sector. This study uses importance performance analysis to identify factors that need to be improved and uses a fishbone diagram to identify the root causes of low green shipping performance. Data collection was carried out through distributing questionnaires and in-depth interviews with shipping industry players in Indonesia. The results of the study indicate that the main factors that hinder the implementation of green shipping are the lack of understanding and awareness of human resources, high costs for implementing environmentally friendly technology, limited availability of environmentally friendly fuels, and lack of supervision and law enforcement. Recommendations for improvements provided include the development of training and awareness campaigns, investment in green technology, improvement of alternative fuel infrastructure, and strengthening supervision and law enforcement related to environmental impacts. This study contributes to designing strategic steps that can improve green shipping in Indonesia.